2017
DOI: 10.1038/srep44482
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional control of IL-23/Th17-mediated autoimmune disease through HO-1/STAT3 activation

Abstract: The nutritional curcumin (CUR) is beneficial in cell-mediated autoimmune diseases. The molecular mechanisms underlying this food-mediated silencing of inflammatory immune responses are poorly understood. By investigating antigen-specific immune responses we found that dietary CUR impairs the differentiation of Th1/Th17 cells in vivo during encephalomyelitis and instead promoted Th2 cells. In contrast, feeding CUR had no inhibitory effect on ovalbumin-induced airway inflammation. Mechanistically, we found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 61 publications
0
19
0
Order By: Relevance
“…Following the decreased DNA-binding activity of STAT3, also the expression of IL-1β and TNF-α were significantly downregulated after treatment with curcumin [ 63 ]. More recently, low concentrations (7.5 μM) of curcumin have been found to induce in vitro an anti-inflammatory profile in DCs enhancing the phosphorylation and the activity of STAT3, thus suggesting a biphasic effect of curcumin on STAT3 modulation depending on the range of curcumin concentrations [ 64 ]. This observation is quite intriguing and has been also observed when curcumin has been used together with opioids, the drugs of choice for the alleviation of acute and chronic pain and opioid tolerance.…”
Section: Curcuma Longamentioning
confidence: 99%
“…Following the decreased DNA-binding activity of STAT3, also the expression of IL-1β and TNF-α were significantly downregulated after treatment with curcumin [ 63 ]. More recently, low concentrations (7.5 μM) of curcumin have been found to induce in vitro an anti-inflammatory profile in DCs enhancing the phosphorylation and the activity of STAT3, thus suggesting a biphasic effect of curcumin on STAT3 modulation depending on the range of curcumin concentrations [ 64 ]. This observation is quite intriguing and has been also observed when curcumin has been used together with opioids, the drugs of choice for the alleviation of acute and chronic pain and opioid tolerance.…”
Section: Curcuma Longamentioning
confidence: 99%
“…The immunomodulatory effects of DMF in experimental settings of autoimmune inflammatory disorders such as multiple sclerosis (MS) are thought to be mediated through both Nrf2‐dependent and Nrf2‐independent pathways . Pharmacological activation of Nrf2 may be a major strategy against MS, other inflammatory diseases and against cancer . Nrf2 is also important to protect keratinocytes from oxidative damage and DMF is a potent inducer of HO‐1 in human keratinocytes cultured in vitro .…”
Section: Mechanism Of Action Of Dmfmentioning
confidence: 99%
“…In DCs, DMF treatment stimulates apoptosis and DMF has also been shown to inhibit the activation of STAT1 and to impair IL‐12 production; its effect on STAT1 depends on the DCs’ intracellular GSH level . In addition, Nrf2‐dependent induction of HO‐1 enhances STAT3 activation in DC, a negative regulator of Il23a transcription . Additional studies to examine the antioxidant properties of DMF and its consequences on signalling pathways in more depth are desirable.…”
Section: Mechanism Of Action Of Dmfmentioning
confidence: 99%
“…In EAE induced by the MOG-peptide 35–55 in C57BL/6 mice, CD4+ Th17 cells are present both in the periphery and in the inflamed central nervous system [ 50 ] and amelioration of EAE by curcumin treatment was through inhibition of IL-17 production [ 39 ]. Further studies indicated that dietary curcumin inhibited the differentiation of pro-inflammatory Th1/Th17 cells in vivo during encephalomyelitis and instead promoted Th2 cells [ 51 ]. Curcumin appeared to silence IL-23/Th17-mediated pathology in EAE by enhancing HO-1/STAT3 interaction in dendritic cells (DCs) [ 51 ].…”
Section: Curcumin As a Remedy For The Treatment Of Rheumatoid Arthmentioning
confidence: 99%
“…Further studies indicated that dietary curcumin inhibited the differentiation of pro-inflammatory Th1/Th17 cells in vivo during encephalomyelitis and instead promoted Th2 cells [ 51 ]. Curcumin appeared to silence IL-23/Th17-mediated pathology in EAE by enhancing HO-1/STAT3 interaction in dendritic cells (DCs) [ 51 ].…”
Section: Curcumin As a Remedy For The Treatment Of Rheumatoid Arthmentioning
confidence: 99%